Effect of annealing and hydrogenation on optical and electrical properties of DC sputtered Mg-Ni bilayer thin films. (2022) - Jangid, M.K.; Sharma, S.S.; Ray, Jaymin; Jangid, Satish
Highlights: Effect of hydrogenation on optical energy bandgap and conductivity of Mg-Ni thin films. Finding the opportunity to use Mg-Ni thin films as solid state hydrogen storage materials. Hall Effect measurements to elaborate the type of the conductivity in thin film. FE-SEM measurements to confirm uniform deposition and presence of elements in the prepared thin film. Abstract: Mg-Ni (150 nm) bilayer thin films were effectively prepared using the magnetron co-sputtering technique onto the glass and ITO coated glass substrates. In order to get homogeneity in the prepared thin film, annealing of the samples was made at 573 K for an one hour in the vacuum. Afterwards films were hydrogenated at 30 psi H2 for one hour. The optical, electrical and structural properties of Mg-Ni thin film were studied using UV–vis spectroscopy, Keithley electrometer, Hall Effect measurement and Field emission scanning electron microscopy(FESEM) along with energy dispersive Spectroscopy (EDS). The optical bandgap of as-deposited thin film was found 3.85 eV and after annealing it was decreased to 3.79 eV. Furthermore, bandgap increment has been observed for annealed hydrogenated thin films and it was 3.91 eV. The Hall Effect measurements and I-V characteristics of samples show the semiconducting nature ( n -type) of the films and the conductivity increases after annealing and decreases after hydrogenation of the annealed sample. Further, the Hall Effect measurements indicate increment in the Hall mobility of annealed thin films where as it is found to be decreased after hydrogenation of the annealed samples. FE-SEM images represent uniform deposition of thin film. The composition of elements was recorded through energy dispersive X-ray spectroscopy (EDAX). Accumulation of hydrogen, particularly at the thin film's interface, blocks the flow of electrons that results in decreased conductivity of thin film after hydrogenation. Therefore, it may be concluded that Mg-NI thin films are suitable for solid state hydrogen storage.